Deconditioning, fatigue and impaired quality of life in long-term survivors after allogeneic hematopoietic stem cell transplantation. (March 2018) - Dirou, Stéphanie; Chambellan, Arnaud; Chevallier, Patrice; Germaud, Patrick; Lamirault, Guillaume; Gourraud, Pierre-Antoine; Perrot, Bastien; Delasalle, Béatrice; Forestier, Bastien; Guillaume, Thierry; Peterlin, Pierre; Garnier, Alice; et al.
Abstract Long–term survivors after allogeneic hematopoietic stem cell transplantation (allo-HSCT) are at high risk for treatment-related adverse events, that may worsen physical capacity and may induce fatigue and disability. The aims of this prospective study were to evaluate exercise capacity in allotransplant survivors and its relationship with fatigue and disability. Patient-reported outcomes and exercise capacity were evaluated in 71 non-relapse patients 1 year after allo-HSCT, using validated questionnaires, cardiopulmonary exercise testing (CPET) with measure of peak oxygen uptake (peakVO2 ) and deconditioning, pulmonary function testing, echocardiography and 6-min walk test. A high proportion (75.4%) of allo-HSCT survivors showed abnormal cardiopulmonary exercise testing parameters as compared to predicted normal values, including 49.3% patients who exhibited moderate to severe impairment in exercise capacity and 37.7% patients with physical deconditioning. PeakVO2 values were not accurately predicted by 6-min walk distances (r  = 0.53). Disability and fatigue were strongly associated with decreased peakVO2 values (p  = 0.002 andp  = 0.008, respectively). Exercise capacity was reduced in most allo-HSCT long-term survivors. Because reduced exercise capacity was associated with fatigue, disability and a decrease in quality of life, cardiopulmonary exercise testing should be performed in every patient who reports fatigue and disability.